Объяснение:
8.
Замена:
Обратная замена:
9.
По теореме Виета:
Второй корень: x₂= 5 · 2 = 10.
10.
Отдельно перемножим первый и четвертый, второй и третий множители:
В этом случае корней нет.
Итого: x₁ =-4, x₂ = 1.
Объяснение:
8.![x^4-9x^2+20=0](/tpl/images/1047/6908/39521.png)
Замена:![x^2=t\geq 0](/tpl/images/1047/6908/da421.png)
Обратная замена:![\left [ {{x^2=4,} \atop {x^2=5;}} \right. \left [ {{x=\pm 2,} \atop {x = \pm \sqrt5 ;}} \right.](/tpl/images/1047/6908/6f8e6.png)
9.![x^2-12x+q=0, \frac{x_1}{x_2} =\frac{1}{5} \Rightarrow x_2 =5x_1\\](/tpl/images/1047/6908/91e64.png)
По теореме Виета:![\left \{ {{x_1+x_2=12} \atop {x_1x_2=q}} \right.\left \{ {{x_1+5x_1=12} \atop {x_1\cdot 5x_1=q}} \right.\left \{ {{6x_1=12} \atop {5x_1^2=q}} \right. \left \{ {{x_1=2} \atop {q=5\cdot2^2}} \right. \Rightarrow q = 20.](/tpl/images/1047/6908/64275.png)
Второй корень: x₂= 5 · 2 = 10.
10.![x(x+1)(x+2)(x+3)=24 \\](/tpl/images/1047/6908/dda3b.png)
Отдельно перемножим первый и четвертый, второй и третий множители:
Замена:![x^2+3x=t](/tpl/images/1047/6908/c4ff4.png)
Обратная замена:![\left [ {{x^2+3x=-6,} \atop {x^2+3x=4}} \right. \left [ {{x^2+3x+6=0}(1)\atop {x^2+3x-4=0}(2)} \right.](/tpl/images/1047/6908/2963e.png)
Итого: x₁ =-4, x₂ = 1.